Transformational Leadership and Employees' Performances: The Mediating Role of Motivation and Work Environment - Yunianto Agung Nugroho; Masduki Asbari; Agus Purwanto; Sucipto Basuki; Rachma Nadhila Sudiyono; Muhamad Agung Ali Fikri; Paolinus Hulu; Mustofa Mustofa; Gusli Chidir; Suroso Suroso; Yos Xavir (EduPsyCouns: Journal of Education, Psychology and Counseling, 2020)
The purpose of this study is to measure the effect of a transformational leadership and on employees’ performance in an Indonesian manufacturer through motivation and work environment as a mediating variables. Data were collected by using simple random sampling to 851 employees population in an Indonesia manufacturer. The number of returned and valid questionnaires was 627. Data were processed by using SEM with SmartPLS 3.0. The results of the study concluded that transformational leadership has a positive and significant effect on employees’ performance, both directly and indirectly through a mediating effect of motivation and work environment. This study proposes a model to improve employees’ performance in Indonesia manufacturers by a transformational leadership through motivation and work environment as a mediator. This study can open the way to improve employee readiness in facing industrial revolution 4.0.